Capturing Heterogeneity in Medical Marijuana Policies: A Taxonomy of Regulatory Regimes Across the United States - Chapman, Susan A. (Subst Use Misuse, 2016)
BACKGROUND: There is considerable movement in the U.S. to legalize use of cannabis for medicinal purposes. Twenty-three U.S. states and the D.C. have laws that decriminalize use of marijuana for medicinal purposes. Most prior studies of state medical marijuana laws and their association with overall marijuana use, adolescent use, crime rates, and alcohol traffic fatalities, have used a binary coding of whether the state had a medical marijuana law or not. Mixed results from these studies raise the question of whether this method for measuring policy characteristics is adequate. OBJECTIVES: Our objective was to develop a validated taxonomy of medical marijuana laws that will allow researchers to measure variation in aspects of medical marijuana statutes as well as their overall restrictiveness. METHODS/RESULTS: We used a modified Delphi technique using detailed and validated data about each state's medical marijuana law. Three senior researchers coded elements of the state laws in initiation of use, quantity allowed, regulations around distribution, and overall restrictiveness. We used 2013 NSDUH data to assess validity of the taxonomy. Results indicate substantial state-level variation in medical marijuana policies. Validation analysis supported the taxonomy's validity for all four dimensions with the largest effect sizes for the quantity allowed in the state's medical marijuana policy. CONCLUSIONS/IMPORTANCE: This analysis demonstrates the potential importance of non-dichotomous measurement of medical marijuana laws in studies of their impact. These findings may also be useful to states that are considering medical marijuana laws, to understand the potential impact of characteristics of those laws.